Retrospective study of the medium‐chain acyl‐CoA dehydrogenase deficiency in Portugal. (28th July 2013) - Ventura, F.V.; Leandro, P.; Luz, A.; Rivera, I.A.; Silva, M.F.B.; Ramos, R.; Rocha, H.; Lopes, A.; Fonseca, H.; Gaspar, A.; Diogo, L.; Martins, E.; et al.
<x xml:space="preserve">Abstract</x> Medium‐chain acyl‐CoA dehydrogenase deficiency (MCADD) is the commonest genetic defect of mitochondrial fatty acid β‐oxidation. About 60% of MCADD patients are homozygous for the c.985A>G (p.Lys329Glu) mutation in the ACADM gene (G985 allele). Herein, we present the first report on the molecular and biochemical spectrum of Portuguese MCADD population. From the 109 patients studied, 83 were diagnosed after inclusion of MCADD in the national newborn screening, 8 following the onset of symptoms and 18 through segregation studies. Gypsy ancestry was identified in 85/109 patients. The G985 allele was found in homozygosity in 102/109 patients, in compound heterozygosity in 6/109 and was absent in one patient. Segregation studies in the Gypsy families showed that 93/123 relatives were carriers of the G985 allele, suggesting its high prevalence in this ethnic group. Additionally, three new substitutions—c.218A>G (p.Tyr73Cys), c.503A>T (p.Asp168Val) and c.1205G>T (p.Gly402Val)—were identified. Despite the particularity of the MCADD population investigated, the G985 allele was found in linkage disequilibrium with H1(112) haplotype. Furthermore, two novel haplotypes, H5(212) and H6(122) were revealed.